PEMANFAATAN JAMUR NEUROSPORA CRASSA DALAMPEMBUATAN RANGEN KUKUS GUNA PENINGKATANGIZI DAN KESEJAHTERAAN MASYARAKAT - Rani Asri W., Heni Mahzumi, Fatwa Ika W., M. Noorcahya Eka S., dan Wasilah (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
This research aims to know 1) the use of Neurospora Crassa mushroom in the makingof steamed neuros rangen, 2) the influence of Neurospora Crassa in the improving ofprotein, carbohydrate, and fat in this rangen, and 3) the effort of improving the society’shome industry by producing nutritious food which is easily made.The research was conducted by making rangen which is mixed with NeurosporaCrassa. It aims to improve the standard of nutrition especially fat, protein, andcarbohydrate. There were three methods used in this research; kjeldhal method to knowthe nutritious substances, Nelson method to know the amount of carbohydrate, andEther extraction to know the amount of fat.The result of the research shows that the use of Neurospora Crassa results in theincreasing of protein (0,42%), carbohydrate (11,507mg/ml), and fat (0,4725%).Keyword: Neurospora Crassa Mushroom, protein, carbohydrate, and fat.